Pengaruh Matematika terhadap Motivasi dan Prestasi Belajar Mahasiswa Jurusan Akuntansi Universitas Bina Nusantara - Pariang Siagian (Binus Business Review, 2013)
For learning achievement, it is acknkowledged that there are many factors influencing such as internal motivation from students, like willingness or motivation, self discipline and another important thing is level of intelligence. The background of this research  is lot of students are not able to follow  the lessons well, and  the effect is they face some difficulties on their academic achievement, including the areas of accounting subject loaded with mathematic or counting subject. Many students are not happy about math subject, so it makes them less of motivation to learn, and ultimately affects the achievement. Therefore, the writer is interested in conducting research presented in this paper. The factor on this research is to determine whether the influence of mathematic on learning motivation and learning achievement for the students majoring in Accounting Students of Economic hoping to improve the quality of learning process in producing quality graduates. Population on this research is all Accounting Department students, Bina Nusantara University. Research method used is parametric statistic, with purposive sampling, and in processing data is SPSS method with regression analysis tool.  From the research, it is concluded 1) there is significant effect of mathematic factor to the learning motivation, and 2) there is not the significant effect of mathematic factor to the learning achievement.